Effect of metformin on sepsis-associated acute lung injury and gut microbiota in aged rats with sepsis - Wan, Youdong; Wang, Shuya; Niu, Yifan; Duo, Boyang; Liu, Yinshuang; Lu, Zhenzhen; Zhu, Ruixue (Frontiers in Cellular and Infection Microbiology, 2023)
Recent studies indicate an association between the changes in intestinal flora and sepsis, but the potential mechanisms underlying sepsis-associated acute lung injury (SALI) are still unclear. This study aimed to investigate the effect of metformin on intestinal microbiota and ASLI in aged rats with sepsis. It also explored the therapeutic mechanism and the effect of metformin on aged rats with SALI. Twenty-four rats aged 20-21 months were randomly categorized into three groups: sham-operated rats (AgS group), rats with cecal ligation and puncture-induced sepsis (AgCLP group), and rats treated with metformin (25 mg/kg) orally 1 h after AgCLP treatment (AgMET group). We collected feces from rats and analyzed them using two methods: 16S rRNA sequencing and untargeted metabolomics using liquid chromatography–tandem mass spectrometry. Further, the lung and kidney tissues were collected.This study showed that some pathological changes occurring in the lungs of aged rats, such as hemorrhage, edema, and inflammation, improved after metformin treatment. Some genera were positively correlated with the inflammatory factors, including Klebsiella, Escherichia coli, and Prevotella-9. Also, metformin played a role in reversing the changes in this type of microbiota. We found that metformin reduced lung injury in aged rats with sepsis by affecting the intestinal flora, which in turn reduced the inflammatory response and might effectively treated SALI. Metformin could improve SALI and intestinal flora in aged rats with sepsis, which could provide a potential therapeutic treatment for SALI in aged sepsis.